2014
DOI: 10.2166/wst.2014.221
|View full text |Cite
|
Sign up to set email alerts
|

UV/TiO2 photocatalytic oxidation of recalcitrant organic matter: effect of salinity and pH

Abstract: Photocatalytic oxidation processes have interest for water treatment since these processes can remove recalcitrant organic compounds and operate at mild conditions of temperature and pressure. However, performance under saline conditions present in many water resources is not well known. This study aims to explore the basic effects of photocatalysis on the removal of organic matter in the presence of salt. A laboratory-scale photocatalytic reactor system, employing ultraviolet (UV)/titanium dioxide (TiO₂) phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In order to elucidate the role of TiO 2 catalyst and UV light as well as their combined effects on the HA degradation, experiments were performed for 2 h with different experimental conditions (UV, TiO 2 , and UV/TiO 2 ) using an initial HA concentration of 20 mg/L at pH 7.5. Previous research [ 26 ] has shown that TiO 2 concentrations of 0.5 and 1 g/L resulted in significant HA removals of up to 83% using HA solution of 20 mg/L with an initial TOC concentration of 7 mg/L which is similar HA concentration as used in this work. Therefore, these TiO 2 concentrations were again used in this work.…”
Section: Methodsmentioning
confidence: 76%
See 1 more Smart Citation
“…In order to elucidate the role of TiO 2 catalyst and UV light as well as their combined effects on the HA degradation, experiments were performed for 2 h with different experimental conditions (UV, TiO 2 , and UV/TiO 2 ) using an initial HA concentration of 20 mg/L at pH 7.5. Previous research [ 26 ] has shown that TiO 2 concentrations of 0.5 and 1 g/L resulted in significant HA removals of up to 83% using HA solution of 20 mg/L with an initial TOC concentration of 7 mg/L which is similar HA concentration as used in this work. Therefore, these TiO 2 concentrations were again used in this work.…”
Section: Methodsmentioning
confidence: 76%
“…More importantly, the combination of photocatalytic oxidation process with physical separation of TiO 2 via a ceramic membrane filtration was explored. This study is an extension of our previous work where the influence of salinity on the removal of HA using UV/TiO 2 photocatalytic process alone was examined [ 26 ]. The purpose of this study is to evaluate the potential for the hybrid process under ideal conditions prior to exploring on municipal wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work described the influence of experimental variables such as solution pH, salinity and TiO 2 dose on the removal of a model HA solution using TiO 2 /UV photocatalytic oxidation process and ceramic membrane filtration [8,24]. These studies showed that relatively high removal of TOC and UV absorbance, removal of HA fouling potential and the complete recovery of TiO 2 slurry using this hybrid system were achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Membrane filtration is not only able to separate suspended catalysts, but can also enhance the effluent quality by selective separation at the molecular level if small pore size memranes are used [6]. Furthermore, semiconductor photocatalysis is able to mineralize compounds causing membrane fouling and thus improve the consistency of the membrane’s operation [4,7,8]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation